Preserved levels of uninvolved immunoglobulins are independently associated with favorable outcome in patients with symptomatic multiple myeloma - Kastritis, E.; Zagouri, F.; Symeonidis, A.; Roussou, M.; Sioni, A.; Pouli, A.; Delimpasi, S.; Katodritou, E.; Michalis, E.; Michael, M.; Hatzimichael, E.; Vassou, A.; et al. (Leukemia, 2014)
Suppression of uninvolved immunoglobulins is common in multiple myeloma (MM) but the prognostic significance of this phenomenon has not been assessed. We evaluated the prognostic significance of the preservation of uninvolved immunoglobulins in 1755 consecutive, unselected, patients with newly diagnosed, symptomatic MM with pre-therapy immunoglobulin levels measured by nephelometry. Suppression of at least one uninvolved immunoglobulin was observed in 87% of patients and was more common in patients with immunoglobulin A myeloma, those aged over 65 years, in patients with advanced-International Staging System (ISS) stage, extensive-bone marrow infiltration, anemia, low platelet counts, high levels of serum M-monoclonal protein or renal dysfunction. Patients with preserved immunoglobulins had a better survival than patients with suppressed immunoglobulins (median survival 55 vs 41.5 months, P<0.001). In multivariate analysis, preservation of uninvolved immunoglobulins was independently associated with better survival (hazard ratio: 0.781, 95% confidence interval: 0.618-0.987, P=0.039); irrespective of the treatment. In a subset of 500 patients, which were strictly followed for disease progression, preservation of uninvolved immunoglobulins was associated with a significantly longer progression-free survival (60 vs 25 months, P<0.001), independently of other common prognostic factors. In conclusion, preservation of uninvolved immunoglobulins in newly diagnosed patients with symptomatic MM was independently associated with long term disease control and improved survival. © 2014 Macmillan Publishers Limited. All rights reserved.